Nutritional value of edible Russula griseocarnosa in Vietnam - Anh, Chung Nhu; Chi, Nguyen Minh; Dell, Bernard (Asian Journal of Agriculture and Rural Development, 2024)
This study examines the nutritional value of edible Russula griseocarnosa in Vietnam. Russula griseocarnosa is a popular edible wild mushroom in northern Vietnam, where it is consumed locally or exported to China. Future market development and increased trade in Russula griseocarnosa require information on the composition and quality of mushrooms being harvested from the wild. As the nutritional value of this mushroom has not been documented, mushrooms were collected from secondary forests in Bac Giang and Cao Bang provinces, and primary forests in Quang Ninh province for determining the proximate and mineral contents. We dried the mushrooms and sequentially measured the proximate content using standard protocols. For mineral content, the mushroom powder was acid digested and analysed by atomic absorption spectrometry. The study found that Russula griseocarnosa in Vietnam contained 18-29% protein, 57-68% carbohydrate, 8.7-13.7% crude fiber, 0.8-2.1% crude fat, and 0.9-1.1% ash, and has high mineral content (mg/kg dry weight) of K (19,836-24,966), P (2,631-3,335), Ca (573-1,530), Mg (350-636), Fe (143-836), Zn (60-93), and Cu (31-42). The data in this study can be used in establishing official product brands of Russula griseocarnosa, which could improve the livelihood of local people who are dependent on non-wood forest products. Further studies should explore the market chain and mushroom product opportunities, the livelihood of rural households, and the sustainability of harvesting wild mushrooms.